Strategi Promosi untuk Homestay di Desa Wisata Pager Harjo Kecamatan Samigaluh, Kab. Kulon Progo, Provinsi Daerah Istimewa Yogyakarta - Ananta Budhi Danurdara; Rudy Parlindungan Siahaan; Lucky Karsuki; Nor Ismawanto Choirudin; Wanti Arum Wanti (Tourism Scientific Journal, 2022)
Kulon Progo Regency has many tourist destinations spread throughout the Kulon Progo Regency, both natural tourism, educational tourism, and religious tourism. One of them is in the Menoreh Mountains which is located in Samigaluh District, especially in the Pagerharjo Village area. Pagerharjo Village is one of the Tourism Villages which has various tourism potentials, both natural panoramas, arts, culture, customs, culinary and so on. To accommodate tourists who come to enjoy tourism potential, many homestays are developing which are still managed by traditional owners so that the occupancy of these homestays is still small. Therefore a marketing strategy is needed, namely the right promotion to increase the occupancy rate of homestay rooms. This research was conducted using a qualitative descriptive method. The results showed that the promotion strategy that had been carried out was not planned in advance, only aimed at family guests and was still carried out using WOM (words of mouth). Promotions carried out through social media (facebook and Instagram) have not been carried out optimally and are not updated continuously. Expansion of the target market and promotional media through social media can be made more active and targeted to increase homestay occupancy rates. Besides, the role of KOMPEPAR/POKDARWIS is very important in assisting homestays so that they can develop promotional strategies that will be and have been carried out.